The intersection of gender, race and cultural boundaries, or why is computer science in Malaysia dominated by women? - Mellstrom, Ulf (2009)
This paper reports an investigation on how and why computer science in Malaysia is dominated by women. Inspired by recent critical interventions in gender and technology studies, the paper aims to open up more culturally situated analyses of the gendering of technology or the technology of gendering, with the Malaysian case exemplifying the core of the argument. The paper argues along four different strands of critical thought: (1) a critique of the analytical asymmetry in the process of co-production in gender and technology studies; (2) a critique of a western bias in gender and technology studies, advocating more context sensitivity and focus on the cultural embeddedness of gender and technology relations; (3) a critique that pays more attention to spatial practices and body politics in regard to race, class and gender in relation to technology; and (4) a critique of `western' positional notions of gender configurations that opens up for more fluid constructions of gender identity, including the many crossovers between relational and positional definitions of femininity and masculinity. - Reproduced.
Keywords: Computer science; Women scientist